Spatial risk for a superspreading environment: Insights from six urban facilities in six global cities across four continents - Loo, Becky P. Y.; Tsoi, Ka Ho; Axhausen, Kay W.; Cao, Mengqiu; Lee, Yongsung; Koh, Keumseok Peter (Frontiers in Public Health, 2023)
This study sets out to provide scientific evidence on the spatial risk for the formation of a superspreading environment. While specific environmental, exposure-related, activity-related and human mobility factors have been examined in isolation, it is only recently that a synthesis of the analysis in specific geographical settings and at a city scale has been conducted. This is the research gap that this study aims to fill. Focusing on six common types of urban facilities (bars, cinemas, gyms and fitness centres, places of worship, public libraries and shopping malls), it first tests whether visitors’ mobility characteristics differ systematically for different types of facility and for different locations. Stemming from classical locational theories, geographers have shown that facility agglomeration is not only associated with external economies of scales but also different social mix of people. The latter has implications on the spatial spread of contagious diseases. In order to establish wider evidence, this study collects detailed human mobility data in six major global cities (Chicago, Hong Kong, London, São Paulo, Seoul and Zurich) across four continents to examine whether visitors’ mobility patterns are consistent. Most of these travel surveys were conducted by governments in a city-wide manner with random sampling strategies. The total number of survey respondents of the six cities is 287,210. Based on the research findings, a kernel density function is employed to derive the risk surface in each city based on the spatial risk class and nature of activities. Finally, it makes recommendations that balance the control of the pandemic and the daily life of the urban population. Thinking beyond complete city lockdowns, a more differentiated and location-sensitive policy of disease control and exit strategies is proposed.